A DETERMINATION OF CRITICAL RISK FACTORS IN THAILAND REAL ESTATE BUSINESS - Khumpaisal, Sukulpat (RMUTT Global Business and Economics Review, 2022)
This study aims to study risk factors affecting the Thai real estate business, as well as study risk level of various risk factors that occur in Thai real estate development, resulting in risk management guidelines for entrepreneurs. Semi-structured interviews were conducted with 15 key informants who are real estate developers in various regions of Thailand, and the risk score was calculated based on the multiplicative likelihood of risk factors and the degree of risk. The findings revealed that the majority of the Thai real estate business’s risk factors were likely to occur, and the level of impact of the risk factors was high. However, when considering the risk rating according to the Stock Exchange of Thailand’s organizational risk management framework, it was discovered that three risk factors of the Thai real estate business had a very high level of risk (risk score is between 16.01 - 25.00) as follows: 1) Customers’ purchasing power/rental has decreased in the current economic climate, 2) liquidity in the disposition of assets is very low, and 3) the land and building tax raises the cost of land, respectively. These three risk factors are an economic factor and a legal factor which uncontrollable external factor and unavoidable factor for Thai real estate entrepreneurs.